2015
DOI: 10.1373/clinchem.2015.240051
|View full text |Cite
|
Sign up to set email alerts
|

24,25-Dihydroxyvitamin D3 and Vitamin D Status of Community-Dwelling Black and White Americans

Abstract: BACKGROUND 24,25-dihydroxyvitamin D (24,25(OH)2D) is a metabolite of 25-hydroxyvitamin D (25D). Blacks frequently have low total 25D without manifestations of vitamin D deficiency, suggesting that total serum 25D may incorrectly reflect vitamin D status in different racial groups. The ratio of serum 24,25(OH)2D to 25D (Vitamin D Metabolite Ratio [VMR]) represents a new candidate biomarker for vitamin D status. METHODS We measured 24,25(OH)2D3 and 25D3 by mass spectrometry in a random community cohort of blac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 36 publications
4
81
1
Order By: Relevance
“…Studies have also shown differences in the relationship between 25-OHD and PTH in Black compared to White subjects. While Blacks have serum concentrations of 25-OHD approximately 30% lower than Whites [106][107][108], this is not associated with a proportional increase in PTH. When considering individuals with comparable PTH concentrations, serum 25-OHD is again significantly lower in Blacks than in Whites.…”
Section: -Hydroxy Vitamin D and 125-dihydroxy Vitamin Dmentioning
confidence: 88%
See 1 more Smart Citation
“…Studies have also shown differences in the relationship between 25-OHD and PTH in Black compared to White subjects. While Blacks have serum concentrations of 25-OHD approximately 30% lower than Whites [106][107][108], this is not associated with a proportional increase in PTH. When considering individuals with comparable PTH concentrations, serum 25-OHD is again significantly lower in Blacks than in Whites.…”
Section: -Hydroxy Vitamin D and 125-dihydroxy Vitamin Dmentioning
confidence: 88%
“…Considering there is direct enzymatic conversion of 25-OHD into 24,25-OH 2 D it is not surprising that the concentrations of both compounds are strongly correlated [113]. In contrast to DBP, this correlation is comparable across different races (Blacks: r = 0.86, p < 0.001; Whites: r = 0.90, p < 0.001) [107]. 24,25-OH 2 D possesses some conceptual advantages over DBP, BAVD and 25-OHD.…”
Section: Bioavailable Vitamin D 2425-dihydroxy Vitamin D and Vitamimentioning
confidence: 99%
“…Consequently, the recommended 25(OH)D cut-offs vary between different scientific bodies [7][8][9][10]. Age or gender specific cut-offs are not suggested by any guideline although several studies suggest that physiologic 25(OH)D requirements may vary with age, gender and ethnicity [11][12][13][14][15]. Interpretation of 25(OH) D results is further complicated by a variable accuracy of 25(OH)D assays and a strong seasonal variability of up to 20% [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the relationship between circulating 25(OH)D3 concentrations and clinical outcomes such as osteoporosis and fracture risk may differ between racial groups, raising the question of whether 25(OH)D3 provides a reliable estimate of vitamin D status in all populations [18,19]. For these reasons, increasing attention is being paid to the measurement of 24,25(OH) 2 D3 (the major circulating catabolite of vitamin D), and the ratio of 24,25(OH) 2 D3 to 25(OH)D3, as potential markers of vitamin D catabolism and predictors of the serum 25(OH)D response to vitamin D supplementation [5,6,12,18,20].…”
Section: Introductionmentioning
confidence: 99%